Competitiveness of Kaili Ethnic Human Resources in Indonesia - Falih Suaedi, Indah Ahdiah, I.B Wirawan, Bagong Suyanto, Subagyo Adam, (Opción, 2019)
This research aims to explore the understanding of ethnic Kaili in Indonesia about the supporting factors and inhibiting the competitiveness of human resources via comparative qualitative research methods. As a result, the supporting components and inhibiting factors of competitiveness of Kaili ethnic human resources are caused by natural, religious, cultural, economic, and political factors. In conclusion, understanding the social knowledge of a community about the competitiveness of human resources will result in an appreciation of the rich diversity of cultural values throughout the world.